Cosolvent effect on morphogenic changes of self-assembled aggregates from biodegradable polylactones. Issue 10 (27th September 2022) - Mandal, Piyali; Mukherjee, Madhumita; Shunmugam, Raja
Abstract: The solvent variation effect on the self-assembly phenomenon is discussed in this article. Two different biodegradable backbones of the same community (polycaprolactone and polylactide) were selected to visualize the morphological changes upon treatment of different solvents/cosolvents. The curiosity was to observe if the change occurred only with the solvents or it was assisted to the backbones also. Tetrahydrofuran, acetonitrile and 1, 4 dioxane were used as polar aprotic solvent whereas, methanol was used as polar protic one with the common solvent water in each case. The macromolecular aggregates were formed using the solvent mixture and their morphological or conformational changes were monitored using different conventional techniques such as Dynamic Light Scattering (DLS), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and cryo-Transmission Electron Microscopy (cryo-TEM).The spontaneously formed superstructures were thoroughly characterized and well documented here. The hierarchical aggregates disclosed here bears the potential of vast usage in the field of nanotechnology. Graphical Abstract: Super-aggregated nanostructures of biodegradable lactones derived thiobarbiturate homopolymers in different solvent mixtures UF0001